Grief-Writing: Navigating Ecological Suffering Through a Relational Pedagogy - Latremouille, Jodi (Art/Research International, 2022)
It’s been a tough couple of years. Each one among us could list off the news headlines as a lengthy and overwhelming reminder. And each one among us could certainly curate a personalized list that amplifies and extends our collective sufferings. The past couple of years have left me wondering, “what could possibly be next?” I heed David Geoffrey Smith’s (2014) call to “reimagine new, wiser human possibilities” for our overlapping worlds of suffering. As an educator, mother, world-lover deeply concerned with all forms of justice, I share grief-writing: poetic stories of small-town sufferings through floods, stories of family hurts, heartaches and loss, stories of love enduring through hopelessness. I engage life writing and poetic inquiry to undertake a dialogue with my own heart-memories, my loved ones, my scholarly ancestors— towards hopeful pedagogical possibilities for healing.